Effects of Tramadol and Tilidine/Naloxone on Oral-Caecal Transit and Pupillary Light Reflex - Freye, Enno; Latasch, Leo (Arzneimittelforschung, 2000)
As has been demonstrated in binding studies the two opioids tilidine (CAS 27107-79-7)/na-loxone (CAS 357-08-4) and tramadol (CAS 36282-47-0) differ in regard to their affinities to the opioid receptor site. Therefore it is of interest to evaluate whether such a difference in opioid affinity is also seen in the pharmacological effects of clinically relevant doses in man. Following institutional approval by the local ethical committee and informed consent, 12 volunteers received oral doses of tramadol (100 mg), tilidine/naloxone (100 mg) and placebo, respectively, in a randomized, double-blind cross-over design. In order to determine the degree of constipation, oral-caecal transit time was measured using the H2-exhalation test. Additionally, in order to evaluate a centrally mediated effect, the response of the pupil to light was quantified using the pupillary light reflex technique. Both, peripheral and central mediated effects were compared to placebo.Tramadol as well as tilidine/naloxone induced a significant (p < 0.05) prolongation of oral-caecal transit when compared to placebo. However, prolongation of oral-caecal transit was significantly longer in the tilidine/naloxone (p < 0.05) than in the tramadol group. Compared to tramadol, the pronounced constipating effect of tilidine/naloxone is likely to be due to the 10 fold higher affinity of that drug to the peripheral opioid receptor sites in the intestinal tract, which are responsible for normal propulsion. Such difference in binding is underlined by a central effect, the pupillary light reflex response. The amount of constriction of the iris to light was reduced after both opioids. Again, tilidine/naloxone significantly reduced (p < 0.001) the pupillary light reflex when compared to tramadol.Other side effects such as tiredness, nausea, emesis and dry mouth were more often reported after tilidine/naloxone than after tramadol (40% versus 15%; p < 0.05). Vertigo and perspiration were more often reported after tramadol than after after tilidine/naloxone (58% and 78% versus 8%; p < 0.01). All these data support the findings that while tramadol is considered an opioid, it does not mediate its main clinical relevant properties via binding at the opioid receptor. More likely, due to its monoaminergic reuptake mechanism, to a lesser extent opioid-like effects are induced.
Keywords: CAS 357-08-4; CAS 27107-79-7; CAS 36282-47-0; Naloxone; Tilidine/na-loxone, effects on oral-caecal transit and pupillary light reflex; Tramadol, effects on oral-caecal transit and pupillary light reflex